Surveillance for Acute Respiratory Illnesses in Pediatric Chronic Care Facilities. Issue 1 (11th October 2022) - Saiman, Lisa; Prill, Mila M; Wilmont, Sibyl; Neu, Natalie; Alba, Luis; Hill-Ricciuti, Alexandra; Larson, Elaine; Whitaker, Brett; Lu, Xiaoyan; Garg, Shikha; Gerber, Susan I; Kim, Lindsay
Abstract: Overall, 119 (33%) of 364 pediatric chronic care facility residents experienced 182 acute respiratory illnesses (ARIs) that met the surveillance definition which led to 31 (17%) emergency room visits, 34 (19%) acute care hospitalizations, and/or 25 (14%) ICU admissions. Continued PCR-positivity was observed in 35% of ARIs during follow-up testing.